The impact of tall fescue (Festuca arundinacea) endophyte (Neotyphodium spp) on non target soil microorganisms - Sayer, S.; Burch, G.; Sarathchandra, S.U. (New Zealand Plant Protection, 2004)
The impact of two strains of the tall fescue (Festuca arundinacea) endophyte (Neotyphodium spp) (E) on the rhizoplane and rhizosphere soil microorganisms was examined at two sites (Lincoln endophytefree (E) and the endophyte strain AR501; and Aorangi E AR501 and a second strain AR542) Rhizosphere and rhizoplane populations of bacteria and fungi functional diversity root fungi and soil microbial biomass carbon and nitrogen were measured Most characteristics measured showed no differences between E and E samples indicating that the presence of endophytes had no impact on nontarget soil microorganisms At Aorangi soil microbial biomass C and N were significantly greater (Plt;005) in AR542 than E1 and AR501 soils Culturable fungal populations from both the rhizoplane and rhizosphere soil were significantly greater (Plt;005) in the E than the AR501 samples at Lincoln but not at Aorangi There were no differences in the functional diversity of rhizoplane microorganisms due to endophyte